Implementing problem-based learning at the Faculty of Veterinary Medicine, Universiti Putra Malaysia - Iskandar, Che Teh Fatimah Nachiar; Arshad, Siti Suri; Dhaliwal, Gurmeet Kaur; Yusoff, Rosnina; H., Kalthum; G., Shanti (Universiti Putra Malaysia Press, 2004)
PBL was introduced into the Doctor of Veterinary Medicine (DVM) curriculum in 2002, at the Faculty of Veterinary Medicine. A steering committee was appointed to plan and implement PBL. Preparation of faculty members included awareness seminars, attending PBL sessions, case vetting sessions, discussions with faculty members at the medical faculties of two local universities and briefing on the role of facilitators. Students were assessed on attendance, communication skills, and content discussions. Students found PBL beneficial in improving their thought and learning process, made them think critically and enable them to integrate knowledge. It also made them realised the importance of understanding rather than memorizing facts. Furthermore, they learned to work as a team. The facilitators found it to be a novel experience having to keep quiet and not interrupt the discussions. The formulation of a case is best done by people familiar with the different aspects of the case and should start by identifying the concept and learning objectives.